KOMPARASI KEKUATAN TEKUK PADA KOMPOSIT LAMINA DENGAN MATRIK DUA JENIS KAYU DAN REINFORCEMENT BAMBU - Sofyan Djamil Djamil (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
Natural materials are environmentally friendly materials that can be made as components of matrix and reinforcement. Wood is part of the stem or branches and twigs of hardened plant due to lignification. Bamboo is a type of grass plants belonging to the order Graminae, familia Bambuseae, rooted fibers, the trunk-shaped cylinder with a diameter that varies from base to tip, hollow, hard. The composite is a composite of two or more materials that are integrated macroscopically and form a new properties. The composite type used in the laminate composite consists of two different layers of material and combined together, using adhesive, the manufacturing process using the hand lay up method. Matrix used balsa and mahoni wood, for reinforcement used type of bamboo apus molded basket woven. Bending test, using ASTM D7264 / D7264M-07 standard. The results of the experiment by testing each test, using 3 test specimens, then taken the average value. For balsa wood matrix, with plain woven reinforcement, buckling strength with value 35.60 ± 2.30 MPa, for balsa wood matrix, with basket woven reinforcement, buckling strength with value 32.64 ± 4.20 MPa. For mahoni matrix, with plain woven reinforcement, buckling strength of 55.15 ± 4.89 MPa, for mahoni matrix, with basket woven reinforcement, buckling strength of 77.15 ± 4.88 MPa. From these data shows that by using mahoni matrix the buckling strength is greater than using balsa wood matrix, either using plain or basket woven.